Correlação entre carga externa, creatina quinase e temperatura da pele em jogadores de futebol - Thiago Vinícius de Almeida Santos (2024)
Due to the relationship between training load, injuries, and performance, monitoring training loads has become essential in high-performance football. Although creatine kinase (CK) and infrared thermography (IRT) are effective for this purpose, their high cost can be a limitation for some clubs. Conversely, GPS presents a more accessible option. The aim of this study was to analyze the correlation between external load measured by GPS and creatine kinase (CK) and skin temperature of the lower limbs in football players after official matches. Sub-20 athletes from a first-division Brazilian football club were evaluated 24 and 48 hours after official matches. Data on GPS, serum CK concentration, and skin temperature of the lower limbs were collected. No significant correlations were found between GPS variables (total distance [DT], distance above 20 km/h [DAI], distance above 25 km/h [DAI2], high-intensity actions [AAI]) and increases in CK and IRT values at any of the evaluated time points. Furthermore, the study revealed that CK levels and IRT values increased significantly 24 and 48 hours after matches compared to baseline values, with a peak at 24 hours (p < 0.05). These results suggest that using only external load does not allow for an indirect estimation of muscle damage and physiological changes in players 24 and 48 hours after matches. Thus, it is concluded that the temperature profile (Tp) of the lower limbs exhibits a similar pattern to CK over time, with an increase 24 hours after matches and a tendency to decrease 48 hours post-match, but still not sufficient to return to baseline condition.